Theoretical Perspectives for Employer Branding - BENDARAVIČIENĖ, Rita (Journal of Advanced Research in Management, 2017)
Employer branding literature – both scholarly and practitioner – has seen many attempts to define employer branding and this variety, albeit enriching, involves terminological ambiguity and therefore calls for elaboration on this term as well as its theoretical framing. Therefore, this paper brings the discussion about theoretical underpinnings upon which employer branding research could be based. Specifically, the theory of psychological contract, the concept of brand equity, signaling theory, literature of organizational ecology and organizational attractiveness construct are linked, reviewed and integrated for better understanding of employer branding.